Corporate Social Responsibility as a Moderating of Good Corporate Governance and Financial Performance on Islamic Social Reporting - Nunung Aini Rahmah; Ali Rahman Reza Zaputra; Ifan Wicaksana Siregar (Fakultas Ekonomi dan Bisnis Islam, 2025)
Islamic Social Reporting (ISR) plays an important role in promoting transparency and accountability in Islamic banking in line with Islamic principles. However, variations in ISR disclosure among Islamic banks in Indonesia indicate the need to identify key factors influencing its quality. This study examines the effects of Good Corporate Governance (GCG) and financial performance on ISR disclosure, with Corporate Social Responsibility (CSR) positioned as a strategic and moderating variable. Using a quantitative approach, this study applies Partial Least Squares–Structural Equation Modeling (PLS-SEM) to panel data from 13 Islamic commercial banks in Indonesia over the period 2020–2023, resulting in 52 observations. ISR and CSR are measured using disclosure indices based on content analysis of annual and sustainability reports, while financial performance is proxied by Non Performing Financing (NPF). The results show that CSR has a strong and significant positive effect on ISR disclosure, indicating that CSR is the primary driver of sharia-based social transparency. In contrast, GCG and financial performance do not have a significant direct effect on CSR. Moreover, CSR does not moderate the relationship between GCG and ISR, suggesting that CSR functions as an independent determinant rather than a reinforcing mechanism of governance. These findings imply that ISR quality in Indonesian Islamic banks is driven more by ethical commitment and sharia obligations embedded in CSR practices than by formal governance structures or financial conditions. This study contributes to the literature by highlighting the central role of CSR in shaping ISR disclosure and provides practical implications for strengthening CSR integration in Islamic banking.